Employing optical microscopy technique to determine the tissue action of Hamamelis virginiana L., Maytenus ilicifolia Mart. ex Reissek and Casearia sylvestris Sw. tinctures on skin-fixed histological sections of Wistar rats - Renan Marcel Bonilha Dezena; Aline Beraldo Ireno; Gustavo Henrique da Silva (São Paulo State University (UNESP), 2021)
Objective: In this study, we aimed to determine the action of the tinctures of Hamamelis virginiana, Maytenus ilicifolia, and Casearia sylvestris on tissues. For this, we investigated the histological sections of fixed skin tissue of Wistar rats for the changes in collagen and elastic fibers, epithelial cells, conjunctive cells, epidermal attachments, pigments, and granules using the optical microscopy technique. Since in the literature and published articles, the use of in vivo models, such as Wistar rats, is predominant to evaluate the healing action of herbal medicines. Methods: The tinctures of Hamamelis virginiana, Maytenus ilicifolia, and Casearia sylvestris, and ethanol 70% (blank) were used. The tinctures were obtained at 10% (w/v) through percolation using 70% ethanol (v/v) as the extraction liquid. This study was conducted in duplicate for each tincture and different incubation times (4, 24, and 48 h) at 37 °C in an oven. The slides used in this study (Wistar rat skin) were previously processed at the histology laboratory since the waste material was donated to conduct this experiment. The Research Ethics Committee approved the use of animals of the Life Sciences Center of the Pontifical Catholic University of Campinas (PUC-CAMPINAS) under the protocol approval number 367/08. Before initiating the staining process, the slides were removed from the oven, and the tincture deposited on the slides was removed. Weigert staining was performed subsequently. For semi-quantitative analysis, the histological sections were carefully observed, and the number of collagen and elastic fibers was evaluated based on the following scale: (+) normal fiber presence, (−) slight decrease, (− −) moderate decrease, and (− − −) intense decrease. The images were digitally captured to obtain the results using a photomicroscope. Results: The degradation of collagen fibers was best evidenced upon using Hamamelis virginiana tincture, which is concordant with the existing reports in the literature on its healing action via the precipitation of dermal proteins. Maytenus ilicifolia and Casearia sylvestris tinctures exhibited low proteolytic capacity as they only caused degradation of elastic fibers that are more delicate and very different from collagen in their constitution. Therefore, the application of the latter two as healing agents (which acts through precipitating proteins) is limited. Conclusions: This experimental histological model using the optical microscopy technique exhibits the advantage of agility and high efficiency as a simple and powerful approach.